Tantangan dan Perkembangan Otonomi Khusus dalam Peningkatan Pendidikan Dasar di Papua Selatan - Konorop, Simon Yanuarius (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the challenges and developments in the implementation of the Special Autonomy policy in the basic education sector in Merauke Regency and to identify supporting and inhibiting factors in its implementation in order to formulate policy recommendations based on field findings. Using a qualitative descriptive approach with a case study design, this study was conducted in Merauke Regency, South Papua, which represents an area with high geographic, social, and cultural complexity. Data were collected through in-depth interviews, direct observation, and documentation studies of education stakeholders, including Education Office officials, school principals, teachers, traditional leaders, and parents of students. The results of the study indicate that the implementation of Special Autonomy has resulted in progress in infrastructure and access in urban areas, but has not been able to overcome the educational gap in remote areas. The main obstacles include delays in fund distribution, weak managerial capacity, and minimal involvement of indigenous communities. Geographical and cultural factors also complicate policy implementation. This study recommends the need for a more participatory policy approach, strengthening local institutions, and developing a contextual curriculum based on local culture. These findings are expected to be a strategic reference in strengthening affirmative policies in the basic education sector in Papua.